2016
DOI: 10.1177/2380084416661474
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials of Silver Diamine Fluoride in Arresting Caries among Children

Abstract: This review aims to investigate the clinical effectiveness of silver diamine fluoride (SDF) in arresting dental caries among children. A systematic search of publications was conducted with the key words "silver diamine fluoride," "silver diammine fluoride," "silver fluoride," "diamine silver fluoride," or "diammine silver fluoride" as well as their translation in Chinese,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
223
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(254 citation statements)
references
References 20 publications
12
223
0
19
Order By: Relevance
“…And finally, there is a clear need for the continued evolution of well-designed, randomized, clinical trials to produce studies with a low risk of bias during the planning, execution, and reporting of results. Standardization in the presentation of data between studies, 18,51 whether they focus on arrest or prevention, is imperative to be able to combine and translate the data into strong clinical guidelines. As indicated, clinicians need to know how to manage arrested lesions for longer periods, which is important for very young children and imperative for permanent teeth.…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
“…And finally, there is a clear need for the continued evolution of well-designed, randomized, clinical trials to produce studies with a low risk of bias during the planning, execution, and reporting of results. Standardization in the presentation of data between studies, 18,51 whether they focus on arrest or prevention, is imperative to be able to combine and translate the data into strong clinical guidelines. As indicated, clinicians need to know how to manage arrested lesions for longer periods, which is important for very young children and imperative for permanent teeth.…”
Section: Current Evidence On the Efficacy Of Silver Diamine Fluoride mentioning
confidence: 99%
“…A randomised, controlled trial concluded that 38% SDF had a better result than the interim restorative treatment using glass ionomer cements (GICs) to arrest cavitated caries in primary teeth. A systematic review confirmed that 38% SDF was effective in arresting dentine caries in deciduous teeth among children. Additionally, caries removal is not needed before application of SDF, which can simplify treatment procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 2 systematic reviews have been published about professionally applied fluoride treatment [Gao et al, 2016b] and SDF [Gao et al, 2016a]. They both affirmed that SDF is effective in controlling caries progression.…”
mentioning
confidence: 99%
“…We only included RCTs with at least a 12-month follow-up period, which resulted in 11 papers. The recently published review on SDF [Gao et al, 2016a] included 19 papers, but the authors did not set a minimum follow-up period, included the same study (with different follow-ups) in the same meta-analysis, and allowed studies without control groups to be included. Additionally, they included in their search data from the China National Knowledge Infrastructure and Ichusi-web databases resulting in the inclusion of papers written in Chinese and Japanese.…”
mentioning
confidence: 99%
See 1 more Smart Citation